Prevalence of cleft lip and/or cleft palate in Guangdong province, China, 2015–2018: a spatio-temporal descriptive analysis - Pi Guo; Yuliang Chen; Bing Li; Degang Wang; Huazhang Miao; Yingxian Zhu; Qinghui Zeng; Xiaolin Yu; Haisheng Wu; Fenghua Liu (BMJ Open)
Objectives This study aimed to investigate the temporal and spatial characteristics of cleft lip and/or palate based on a large-scale birth defect monitoring database.Methods Data on perinatal infants and children with cleft lip and/or palate defects from 1 January 2015 to 31 December 2018 in Guangdong province of China were collected. The variables including the demographic data, basic family information (address, education level, etc.), the infant’s birth weight, gender and other basic parameters were collected and analysed.Results During the study period, the prevalence of cleft lip and/or palate was 7.55 per 10 000 perinatal infants. The prevalence of cleft lip, cleft palate and cleft lip and palate were 2.34/10 000, 2.22/10 000 and 2.98/10 000, respectively. The prevalence of cleft lip and/or palate showed a pronounced downward trend, reducing from 8.47/10 000 in 2015 to 6.51/10 000 in 2018. We observed spatial heterogeneity of prevalence of cleft lip and/or palate across the study period in Guangdong. In the Pearl River Delta region, the overall prevalence of cleft lip and/or palate was 7.31/10 000, while the figure (7.86/10 000) was slightly higher in the non-Pearl River Delta region (p<0.05). Concerning infant gender, the prevalence was in general higher in boys than girls (p<0.05). In addition, the higher prevalence was more common in mothers older than 35 years old. For the birth season, infants born in spring tended to have a higher prevalence than those born in other seasons, regardless of the prevalence of cleft lip and palate calculated separately or jointly (p<0.05). The majority of newborns with cleft lip and palate were accompanied by other birth defects.Conclusion This study contributes a better understanding of the characteristics of spatio-temporal trends for birth defects of cleft lip and/or palate in south China.